KNOWLEDGE OF ANTICIPATED DRUG USE FOR CHILDREN UNDER 5 YEARS OLD CHILDREN IN TWO COMMUNITIES, KIEN XUONG DISTRICT, THAI BINH PROVINCE 2020 (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the current state of caregivers’ knowledge of using antibiotics for children under 5 years old in two communes, Kien Xuong district, Thai Binh province by 2020. Study object: Caregivers in two communes of KienXuong district, Thai Binh.Research method: Epidemiological method described through cross-sectional investigation with analysis.Research results: Percentage of subjects with knowledge of using antibiotics accounts for 68.5%. In which, the percentage of subjects who have ever heard of information about using antibiotics accounted for 87.8%. The research subjects’  knowledge of how to handle when the child’s disease status is reduced is to stop antibiotics as soon as the child’s disease status decreases, accounting for 73.5%. The proportion of respondents who believe that using antibiotics requiresa doctor’s prescription is 60.3%
Keywords: Antibiotics, children under 5 years old